Treatment of hepatitis C virus genotype 3 infection with direct-acting antiviral agents - Zanaga,L.P. (2016)
Hepatitis C virus (HCV) genotype 3 is responsible for 30.1% of chronic hepatitis C infection cases worldwide. In the era of direct-acting antivirals, these patients have become one of the most challenging to treat, due to fewer effective drug options, higher risk of developing cirrhosis and hepatocellular carcinoma and lower sustained virological response (SVR) rates. Currently there are 4 recommended drugs for the treatment of HCV genotype 3: pegylated interferon (PegIFN), sofosbuvir (SOF), daclatasvir (DCV) and ribavirin (RBV). Treatment with PegIFN, SOF and RBV for 12 weeks has an overall SVR rate of 83–100%, without significant differences among cirrhotic and non-cirrhotic patients. However, this therapeutic regimen has several contraindications and can cause significant adverse events, which can reduce adherence and impair SVR rates. SOF plus RBV for 24 weeks is another treatment option, with SVR rates of 82–96% among patients without cirrhosis and 62–92% among those with cirrhosis. Finally, SOF plus DCV provides 94–97% SVR rates in non-cirrhotic patients, but 59–69% in those with cirrhosis. The addition of RBV to the regimen of SOF plus DCV increases the SVR rates in cirrhotic patients above 80%, and extending treatment to 24 weeks raises SVR to 90%. The ideal duration of therapy is still under investigation. For cirrhotic patients, the optimal duration, or even the best regimen, is still uncertain. Further studies are necessary to clarify the best regimen to treat HCV genotype 3 infection.